Addiction to social networks and emotional intelligence in technical higher education students - Alarcón-Allaín, Giovanni Franklin (2022)
Introduction. Social networks are used by around 3,600 million people, they facilitate communication and promote human ties; but its inappropriate use could cause problems and extreme addiction. Objective: Relate addiction to social networks and emotional intelligence. Method: Correlational study, 279 students of technical-superior level participated; The Social Media Addiction Questionnaire (ARS) and the Wong-Law Emotional Intelligence Scale (EI) were administered. Results: Obsession (ARS) negatively correlates with Use of one’s own emotions and Regulation of emotions; likewise, Lack of control and Excessive use (ARS) with the dimensions Valuation of one’s own emotions, Use of one’s own emotions and Regulation of emotions; but, no factor of the ARS correlates with Valuation of the Emotions of the others; Likewise, men and women do not differ in the ARS, those who have more hours of connection are more likely to show higher scores in network addiction; and, in terms of emotional intelligence, women value the emotions of others more. Conclusions: Addiction to social networks and emotional intelligence are negatively related in almost all their dimensions, but it is an association of low magnitudes.